Detection of toluene degradation in bacteria isolated from oil contaminated soils - Ainon Hamzah,; Arezoo Tavakoli,; Amir Rabu, (Universiti Kebangsaan Malaysia, 2011)
Toluene (C7H8) a hydrocarbon in crude oil, is a common contaminant in soil and groundwater. In this study, the ability to degrade toluene was investigated from twelve bacteria isolates which were isolated from soil contaminated with oil. Out of 12 bacterial isolates tested, most of Pseudomonas sp. showed the capability to grow in 1 mM of toluene compared with other isolates on the third day of incubation. Based on enzyme assays towards toluene monooxygenase, Pseudomonas aeruginosa UKMP-14T and Bacillus cereus UKMP-6G were shown to have the highest ability to degrade toluene. The toluene monoxygenase activity was analysed by using two calorimetric methods, Horseradish peroxidase (HRP) and indole-indigo. Both of the methods measured the production of catechol by the enzymatic reaction of toluene monooxygenase. In the HRP assay, the highest enzyme activity was 0.274 U/mL, exhibited by Pseudomonas aeruginosa UKMP-14T. However, for indole-indigo assay, Bacillus cereus UKMP-6G produced the highest enzyme activity of 0.291 U/ml. Results from both experiments showed that Pseudomonas aeruginosa UKMP-14T and Bacillus cereus UKMP-6G were able to degrade toluene.